PRELIMINARY STUDY ON THE EFFECTIVENESS OF THE PROTOTYPE ELECTRO SADJADDAH AS A TOOLS FOR HELPING A DISABLED PEOPLE - TALIB, SAHARUDDIN; SAIM, AISHAH; JOHAN BUDIMAN, JOHAN LELA ANDIKA (Human Sustainability Procedia, 2018)
This study is to identify the effectiveness of theprototype Electro Sadjaddahas device to help disabled people especially in categories half blind or blind people during their prayer.This is a preliminary study and data was collected through questionnaires which contains twomain sections.A total of 20respondents from Islamic Center, Politeknik Sultan Salahuddin Abdul Aziz Shah areparticipated in this study. Results showed that respondents’ interest has increased by 95% whenusing Electro Sadjaddah. The result show that this prototype can help disabled people to perform the prayer